In Silico Identification of Potential American Cockroach (Periplaneta americana) Allergens - A Ahmed; K Minhas; Namood-; O Aftab; F Sher Khan (Tehran University of Medical Sciences, 2010)
Background: Cockroaches have been recognized as a powerful indoor allergen. Cockroach allergy can be a major factor in serious asthma and nasal allergy. Bioinformatics tools have been developed to identify potential allergens. The present study was conducted to identify potential allergens in Periplaneta americana (Linnaeus). Methods: The study focused on the identification of potential allergens among the characterized proteins of P. americana using web-based and publicly available allergen prediction tools that follow the FAO/WHO guidelines for prediction of allergenic proteins. P. americana protein sequences were retrieved from UniProtKB. The sequences obtained were analyzed using AlgPred. The potential allergens obtained were further analyzed by SDAP for confirmation. Results: Protein sequences (233 cases) of P. americana were obtained from UniProtKB out of which 25 were known allergens. Out of the remaining 208 proteins, 102 potential allergens were predicted by AlgPred. However, only 9 were found to be potential allergens after screening with SDAP. Arginine kinases, RNA polymerase II subunit, parcxpwnx02, peptidyl-prolyl cis-trans isomerase, hemocyanin subunit type I and type II, homologue of Sarcophaga proteinase and alpha amylase  were confirmed to be potential allergens by SDAP. Conclusion: We have identified nine potential allergens in P. americana that may be used as preliminary support for further laboratory experiments.